DAMPAK PNPM PERDESAAN TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA WASIAN DIMEMBE, KECAMATAN KABUPATEN MINAHASA UTARA - Regylia Novica Kaunang; Ventje V. Rantung; Paulus A. Pangemanan (AGRI-SOSIOEKONOMI, 2015)
The aim of this study was to determine the impact of PNPM on the welfare of people in the rural village of Wasian, Dimembe sub-district, North Minahasa District. Data were collected by interview. To de-termine the sample to be interviewed was used the purposive sampling method. The total samples were 22 respondents. Respondents were interviewed consisted of 17 people who live in the old way and relatively disadvantaged while the rest were those live along the new road which is 5 respondents. Parameter welfare of rural communities in this study are based on two main indicators, namely social welfare and economic prosperity. Social welfare include: (1) physical development component; (2) The opinion consisting of: (a) opinions on the impact of development itself and (b) the opinion on the social aspects in the field of educa-tion, information, sports, and social interaction; and (3) the ownership of the house. Economic wellbeing include: increasing the number of family revenue. The results showed PNPM Rural activities have a positive impact on the welfare aspects in terms of both social and economic. From the social point of view include: physical development component which realized 100% in the implementation of the form of roads, bridges, and culverts. Public perception of the existing development that is increasingly good roads that exist in the construction of roads, reduced flooding in the presence of sewers, the ease of crossing the bridge. In the perception of the aspects of education, school children can use to access to school without using the vehicle / motorcycle. In the aspect of the perception of the information, the public is more easily gain access to the information needed special access to various facilities in the community. In the perception of the sport as-pect, namely, the growing functionality of existing sports facilities around the development. In the perception of the society more active social interaction in the interaction between public and scolds greet-ings.Increasing home ownership and existence as well as family receipts also increased or prosperous.